Operation Optimization of Regional Integrated Energy System Considering the Responsibility of Renewable Energy Consumption and Carbon Emission Trading - Feng Li (MDPI AG, 2021)
To “bring carbon emissions to a peak by 2030 and to be carbon-neutral by 2060”, the role of renewable energy consumption and carbon emission trading are promoted. As an important energy consumer of regional energy system, it is necessary for integrated energy system to ensure the low-carbon economic operation of the system. Combined with the responsibility of renewable energy consumption, green certificate trading mechanism, carbon emission rights trading, and China Certified Emission Reduction (CCER), a regional integrated energy system operation optimization model was proposed. The model aims to minimize the total cost of the system, which included with electric bus, thermal bus, and cold bus. Setting different scenarios for the given example, the results show that the optimized model could effectively reduce the operating costs of the system. Moreover, the results also provide an effective reference for the system’s economic and low-carbon operation.